RETRACTED: Interaction of pediatrician, oncologist and therapist in the complex therapy of children’s patients - Musaeva R.M.; Basharov M.M.; Magomedov M.M.; Tserr A.E.; Bashmakova N.S.; Korshagina A.M.; Khabibulla E.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001